Local Excitation of Whistler Mode Waves and Associated Langmuir Waves at Dayside Reconnection Regions. Issue 17 (12th September 2018) - Li, Jinxing; Bortnik, Jacob; An, Xin; Li, Wen; Russell, Christopher T.; Zhou, Meng; Berchem, Jean; Zhao, Cong; Wang, Shan; Torbert, Roy B.; Le Contel, Olivier; Ergun, Robert E.; et al.
Abstract: In the Earth's dayside reconnection boundary layer, whistler mode waves coincide with magnetic field openings and the formation of the resultant anisotropic electrons. Depending on the energy range of anisotropic electrons, whistlers can grow at frequencies in the upper and/or lower band. Observations show that whistler mode waves modulate Langmuir wave amplitude as they propagate toward the X line. Observations of whistler mode wave phase and Langmuir waves packets, as well as coincident electron measurements, reveal that whistler mode waves can accelerate electrons via Landau resonance at locations where E|| is antiparallel to the wave propagation direction. The accelerated electrons produce localized beams, which subsequently drive the periodically modulated Langmuir waves. The close association of those two wave modes reveals the microscale electron dynamics in the exhaust region, and the proposed mechanism could potentially be applied to explain the modulation events observed in planetary magnetospheres and in the solar wind. Plain Language Summary: The Sun's and Earth's magnetic field can merge and reconnect on dayside magnetopause. Using measurements from NASA's MMS spacecraft, we report that a class of electromagnetic wave, named whistler mode wave, coincides with the reconnected magnetic field lines. Besides, those whistlers are observed to modulate the electric field oscillations, known as Langmuir waves. Using high‐resolution wave and particle measurements, we explain that the whistlers are locally excited when electrons from both sides of the magnetopause mix and form an unstable distribution. The modulated Langmuir waves are generated due to localized electron acceleration, which occurs when the velocity of electrons matches that of whistlers in the direction along the magnetic field. The whistler mode waves and associated Langmuir waves can be used as an additional tool to remotely sense the occurrence of magnetic reconnections. Key Points: Whistler mode waves are excited at open field lines where magnetospheric and magnetosheath electrons mix and form an anisotropic distribution Whistler mode waves drive and modulate Langmuir waves as they propagate toward the X line Langmuir waves are excited by localized electron beams that are accelerated by whistlers via Landau resonance